Meningkatkan Minat dan Keaktifan Belajar Peserta Didik Pada Pelajaran Sejarah Melalui Penerapan Pembelajaran Teams Games Tournament (TGT) dengan Media Teka-Teki Silang di Kelas X-12 SMA Negeri 3 Medan - Tampubolon, Marta Rebekka (ALACRITY : Journal of Education, 2024)
This research aims to increase students' active learning in the subject of History through the implementation of Teams Games Tournament (TGT) learning using crossword puzzles in class X-12 at SMA Negeri 3 Medan. The method used in this research is Classroom Action Research (CAR) with a target of 36 students. The indicators used in this research are the teacher's ability to use and apply research media and methods, as well as the results after implementing learning using crossword puzzles. Meanwhile, the techniques used for data collection are observation techniques based on observations, questionnaires and documentation techniques. The results of this research show that in cycle 1, students' learning interest and activeness tend to be low/low due to conventional learning strategies, where students' learning interest shows a percentage of 69.72%. Meanwhile, in cycle 2, students' interest in learning history increased to 81.38%. In this case, students' interest in learning history lessons increased by 11.66%. The application of Crossword Puzzle media in History learning through the Teams Games Tournament (TGT) model can provide good stimulation and stimulus to increase students' learning activity such as listening activity, writing activity, movement activity and emotional activity. The formation of groups or teams in this game encourages activeness to be able to work together quickly because they have to compete with other groups.